2021
DOI: 10.25259/cjhs_47_2020
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical features of the brain of patients with stroke (cerebrovascular accident) relative to types, sites, and shapes using computed tomography scan

Abstract: Objectives: Stroke is becoming a very common disease, giving rise to an increased morbidity and mortality globally; yet, its diagnosis is shrouded in the phrase “cerebrovascular accident.” The objectives of the study were to evaluate the various types, sites, and shapes of stroke presentation using computed tomography (CT) scan. Material and Methods: A total of 500 subjects indicative of stroke referred for cranial CT scans were recruited at the Jos University Teaching Hospital, Jos and the Asi-Ukpo Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…This also agrees with many studies conducted in our locality (Omotoso et al, 2019;Udo-Affah et al, 2021) and across the globe at large, however, among healthy subjects (Omotoso et al, 2019;Paulinus et al, 2019). Unlike in many studies (Golalipour et al, 2005;Fawehinmi et al, 2009;Bernhardt et al, 2017), which were conducted on healthy subjects, the present study was among stroke patients and there was no similar study found or done in this locality, where stroke patients' head types were assessed, however, the findings of the present study agree with the studies mentioned above (Omotoso et al, 2019;Udo-Affah et al, 2021). Like in many other studies (Ilayperuma, 2011;Maina et al, 2011;Terkula et al, 2019), conducted on healthy individuals, sexual dimorphisms were observed in FOD and BPD.…”
Section: Discussionsupporting
confidence: 94%
“…This also agrees with many studies conducted in our locality (Omotoso et al, 2019;Udo-Affah et al, 2021) and across the globe at large, however, among healthy subjects (Omotoso et al, 2019;Paulinus et al, 2019). Unlike in many studies (Golalipour et al, 2005;Fawehinmi et al, 2009;Bernhardt et al, 2017), which were conducted on healthy subjects, the present study was among stroke patients and there was no similar study found or done in this locality, where stroke patients' head types were assessed, however, the findings of the present study agree with the studies mentioned above (Omotoso et al, 2019;Udo-Affah et al, 2021). Like in many other studies (Ilayperuma, 2011;Maina et al, 2011;Terkula et al, 2019), conducted on healthy individuals, sexual dimorphisms were observed in FOD and BPD.…”
Section: Discussionsupporting
confidence: 94%
“…Ischemic stroke (CVA) results from the obstruction of a cerebral artery, resulting from the accumulation of fat leading to atherosclerosis and/ or blood clot [1] Circulation is blocked in a certain brain area, causing ischemia by decreasing neurological function. Due to lack of blood supply to the obstructed area, these events promote the death of nervous tissue [2,3].…”
Section: Introductionmentioning
confidence: 99%